Improved Text Classification for Indonesian Hate Speech Detection: FastText-LSTM Model with Easy Data Augmentation - Wicaksana, Hilman Singgih; Huda, Khairul; Airlangga, Gregorius (Universitas Budi Darma, 2026)
The swift expansion of social media in Indonesia has led to a significant rise in hate speech, highlighting the urgent need for effective automated detection techniques. This research evaluates the performance of the proposed FastText-Long Short-Term Memory with Easy Data Augmentation (FastText-LSTM-WE) compared with the baseline model, FastText-Convolutional Neural Network with Easy Data Augmentation (FastText-CNN-WE). To further investigate the impact of data augmentation, the effectiveness of both FastText-Long Short-Term Memory without Easy Data Augmentation (FastText-LSTM-WO) and FastText-Convolutional Neural Network without Easy Data Augmentation (FastText-CNN-WO) was also assessed. Bayesian Optimization was employed to identify the best hyperparameter configurations for each model. The experiments were carried out on a dataset comprising 14,306 samples while maintaining consistent experimental conditions. Model performance was measured using precision, recall, F1-score, and accuracy derived from the confusion matrix. The results indicate that FastText-LSTM-WE achieved the highest performance, with precision, recall, F1-score, and accuracy of 84.02%, 83.16%, 83.59%, and 81.37%, respectively. These findings demonstrate that the proposed model provides a robust and reliable solution for detecting hate speech within the Indonesian context, thereby improving automated content moderation systems in practical applications.